Brain-machine interface: advances in neuroscience and the development of bioelectrodes - Sousa, Wanderson Silva Macedo de (2022)
Objective: To show the updates in this field of research in recent years. Methodology: This is a narrative review, which consist of more extensive publications. The Pubmed database and the Virtual Health Library (VHL) were used to search for articles.  The following Health Sciences Descriptors (DeCS) and Medical Subject Headings(MeSH) were used : "Brain-Computer Interfaces", "Nervous System", "Cerebrum" and "Neurosciences." Articles published between the years 2017 and 2022, in Portuguese and English addressing brain-machine interface advances were included. Results: 17 articles were found that fit the inclusion criteria, all in English. The research demonstrated significant advances that can be employed in physical motor and sensory rehabilitation processes. Conclusion: The application of different protocols and methods was verified, which can be a hindrance to the replication of future studies; however, there were also advances in the development of biocompatible electrodes from axon extensions, which can reduce the inflammatory process in intracortical implants, and the improvement of coding and decoding by non-invasive methods coupled to different parts of the body.